Comparison of Staphylococcus aureus tolerance between antimicrobial blue light, levofloxacin, and rifampin - Ong, Jemi; Godfrey, Rose; Nazarian, Alexa; Tam, Joshua; Isaacson, Brad M.; Pasquina, Paul F.; Williams, Dustin L. (Frontiers in Microbiology, 2023)
Bacterial biofilms readily develop on all medical implants, including percutaneous osseointegrated (OI) implants. With the growing rate of antibiotic resistance, exploring alternative options for managing biofilm-related infections is necessary. Antimicrobial blue light (aBL) is a unique therapy that can potentially manage biofilm-related infections at the skin-implant interface of OI implants. Antibiotics are known to have antimicrobial efficacy disparities between the planktonic and biofilm bacterial phenotypes, but it is unknown if this characteristic also pertains to aBL. We determined minimum bactericidal concentrations (MBCs) and antibiofilm efficacies for aBL, levofloxacin, and rifampin against Staphylococcus aureus ATCC 6538 planktonic and biofilm bacteria. These data were used to compare efficacy disparity profiles amongst the three independent treatments and a levofloxacin + rifampin combination. aBL had the most significant efficacy disparity between the planktonic and biofilm phenotypes (a 2.5 log10 unit difference). The disparity indicated phenotype might be essential component to consider in using aBL to treat OI implant infections. Future research would benefit from expanding these findings against clinical S. aureus isolates and other bacterial strains.